Relationships with caregivers and mental health outcomes among adolescents living with HIV: a prospective cohort study in South Africa - Shenderovich, Y.; Boyes, Mark; Esposti, M.D.; Casale, M.; Toska, E.; Roberts, K.J.; Cluver, L. (BMC, 2021)
Background: Mental health problems may impact adherence to anti-retroviral treatment, retention in care, and consequently the survival of adolescents living with HIV. The adolescent-caregiver relationship is an important potential source of resilience. However, there is a lack of longitudinal research in sub-Saharan Africa on which aspects of adolescent-caregiver relationships can promote mental health among adolescents living with HIV. We draw on a prospective longitudinal cohort study undertaken in South Africa to address this question. Methods: The study traced adolescents aged 10–19 initiated on antiretroviral treatment in government health facilities (n = 53) within a health district of the Eastern Cape province. The adolescents completed standardised questionnaires during three data collection waves between 2014 and 2018. We used within-between multilevel regressions to examine the links between three aspects of adolescent-caregiver relationships (caregiver supervision, positive caregiving, and adolescent-caregiver communication) and adolescent mental health (depression symptoms and anxiety symptoms), controlling for potential confounders (age, sex, rural/urban residence, mode of infection, household resources), n=926 adolescents. Results: Improvements in caregiver supervision were associated with reductions in anxiety (0.98, 95% CI 0.97–0.99, p=0.0002) but not depression symptoms (0.99, 95% CI 0.98–1.00, p=.151), while changes in positive caregiving were not associated with changes in mental health symptoms reported by adolescents. Improvements in adolescent-caregiver communication over time were associated with reductions in both depression (IRR=0.94, 95% CI 0.92–0.97, p<.0001) and anxiety (0.91, 95% CI 0.89–0.94, p<.0001) symptoms reported by adolescents. Conclusions: Findings highlight open and supportive adolescent-caregiver communication and good caregiver supervision as potential factors for guarding against mental health problems among adolescents living with HIV in South Africa. Several evidence-informed parenting programmes aim to improve adolescent-caregiver communication and caregiver supervision, and their effect on depression and anxiety among adolescents living with HIV should be rigorously tested in sub-Saharan Africa. How to improve communication in other settings, such as schools and clinics, and provide communication support for caregivers, adolescents, and service providers through these existing services should also be considered.